Variabilidade temporal no transporte de sedimentos no rio Ivaí - Paraná (1977-2007) - Leli, Isabel Terezinha [UNESP]; Stevaux, Jose Cândido; Da Nóbrega, Maria Tereza; De Souza Filho, Edvard Elias (My University, 2011)
This paper evaluates the behavior of suspended sediment load of the river Ivaí over a period of 32 years measured by the station further downstream the river (Novo Porto Taquara). The most suitable parameters for this assessment were the annual discharge of suspended sediment and water obtained from SUDERSA. The relationship between the concentration of suspended sediment and discharge of water had not a very good correlation (R 2 = 0,56) and hysteresis effect is quite clear. The justification for this behavior is given by the heterogeneity of the hydrological regime and basin occupation. There were no significant changes in annual flows which have remained the same during the study period. Already the discharge of suspended sediment showed a small gradual decline in which the end of the period (2007), the river carries less than 0.65 Mton at the beginning (1977). This reduction in suspended sediment transported is probably due to changes in soil management for agriculture.
Temporal variability in transportation of sediment in the river Ivaí - Paraná (1977-2007)
Keywords: Basin management; River discharge; River flow; River regime; Suspended sediment